Scapula muscle activations during overhead throwing holds - Oliver, G.; Henning, L.; Plummer, H. (International Journal of Athletic Therapy & Training, 2016)
The purpose of this study was to examine activations of selected scapular stabilizing musculature while performing an overhead throw with a hold (not releasing the ball) in two different throwing positions—standing with a crow hop and kneeling on the ipsilateral knee. Surface electromyography was used to examine activations of throwing side lower trapezius (LT), middle trapezius (MT), serratus anterior (SA), and upper trapezius (UT). Muscle activations were recorded while performing the overhead throw with holds while in two throwing positions. MANOVA results revealed no significant differences between the two throwing conditions and muscle activations of LT, MT, SA, and UT: F(8,124) = .804, p = .600; Wilks`s Lambda = .904, partial n hoch2 = .049. Although no significant differences were observed in the scapular stabilizers between the two conditions, moderate (21-50% MVIC) to high (> 50% MVIC) activations of each muscle were present, indicating that nonrelease throws may be beneficial for scapular stabilization in throwers.